2009
DOI: 10.1007/s00335-009-9216-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loci that regulate healing and regeneration in LG/J and SM/J mice

Abstract: MRL mice display unusual healing properties. When MRL ear pinnae are hole punched, the holes close completely without scarring, with re-growth of cartilage, and reappearance of both hair follicles and sebaceous glands. Studies using (MRL/lpr x C57BL/6)F2 and backcross mice first showed that this phenomenon was genetically determined and that multiple loci contributed to this quantitative trait. The lpr mutation itself, however, was not one of them. In the present study, we examined the genetic basis of healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 44 publications
(77 reference statements)
3
48
0
Order By: Relevance
“…In the current study, real progress has been made in narrowing the quantitative trait intervals by use of the (LG,SM) F34 AIL. An important feature of the present work is that QTLs on chromosomes 9, 10, 11, 14 and 18 discovered in earlier studies (Blankenhorn et al, 2009;Cheverud et al, 2012) were confirmed in the AI line, lending further credence to their role in regenerative healing. New QTLs have been identified on chromosomes 1, 7, 12 and 13 in this study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the current study, real progress has been made in narrowing the quantitative trait intervals by use of the (LG,SM) F34 AIL. An important feature of the present work is that QTLs on chromosomes 9, 10, 11, 14 and 18 discovered in earlier studies (Blankenhorn et al, 2009;Cheverud et al, 2012) were confirmed in the AI line, lending further credence to their role in regenerative healing. New QTLs have been identified on chromosomes 1, 7, 12 and 13 in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Gene expression studies for ear hole closure in LG/J and SM/J mice were previously reported (Blankenhorn et al, 2009). RNA samples were prepared in triplicate from day 0 ear holes and from day 7 ear hole donuts from LG/J and SM/J female mice (3 mm circular blastemas formed around the hole punch).…”
Section: Gene Expression and Function Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Whether SM/J mice possess impaired emergency myelopoiesis remains to be ascertained, and it will entail challenging this strain with other pathogens. Thus far, SM/J mice have been deemed susceptible to blood-stage malaria caused by Plasmodium chabaudi (68), and they are considered a non-healer strain when the ear pinnae are wounded (69). The wound-healing trait is controlled by multiple loci, including a locus Heal4 mapping to distal chromosome 15 and overlapping with Carg5.…”
Section: Discussionmentioning
confidence: 99%
“…This promoter mutation creates a binding site for a transcriptional repressor, Nkx3.2, resulting in reduced gene expression ( 56 ). SM/J mice, however, harbor mutations in a number of other genes ( 57,58 ), complicating analysis of the physiological consequences of low sialidase. We have therefore isolated this mutation from the SM/J mice by backcrossing onto a C57Bl/6 genetic background, generating a hypomorphic sialidase mouse, named B6.SM, which has reduced sialidase protein levels and activity.…”
Section: Propagation Of Hd-ad Containing Mouse Sialidase Genementioning
confidence: 99%